On-the-fly informed search of non-blocking directed controllers. (January 2023) - Ciolek, Daniel; Duran, Matias; Zanollo, Florencia; Pazos, Nicolas; Braier, Julián; Braberman, Victor; D'Ippolito, Nicolas; Uchitel, Sebastian
Abstract: We study directed control of discrete event system expressed as the parallel composition of interacting automata. Solutions that first compose the automata and then compute a controller may result in an exponential blow up. We present a technique that builds the composition on-the-fly guided by a novel domain-independent heuristic, which attempts to discover relevant dependencies between the intervening components. We obtain safe and non-blocking directed controllers, or directors, exploring a reduced portion of the state space. We present the first experimental results on directed control comparing on-the-fly composition with informed search against the original monolithic approach to directed control.